Modelling market diffusion of electric vehicles with real world driving data: German market and policy options - Till Gnann; Patrick Plötz; André Kühn; Martin Wietschel (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
Electric vehicles (EVs) have the potential to reduce green house gas emissions from the transport sector. However, the limited electric range of EVs could impede their market introduction. Still some potential users are willing to pay more for EVs. The combined effect of these and other influencing factors as well as the resulting future market evolution are unclear. Here, we study the market evolution of EVs in Germany until 2020. Our results reveal a great deal of uncertainty in the market evolution of EVs due to external conditions and the users' willingness to pay. We find the future share of EVs in German passenger car stock to range from 0.4% to almost 3% by 2020. Energy prices have a large impact on EV market evolution as a 25% increase in fuel prices would double the number of EVs in stock by 2020 compared to a reference scenario. The high uncertainty of the market evolution implies that policies to foster market diffusion of EVs should be dynamically adaptable to react to changing framework conditions. We find a special depreciation allowance for commercial vehicles and a subsidy of 1,000 Euro as the most effective and efficient monetary policy options.
urn:nbn:de:0011-n-3037040
Keywords: 330